A near infrared spectroscopic assay for stalk soluble sugars, bagasse enzymatic saccharification and wall polymers in sweet sorghum. (February 2015) - Wu, Leiming; Li, Meng; Huang, Jiangfeng; Zhang, Hui; Zou, Weihua; Hu, Shiwei; Li, Ying; Fan, Chunfen; Zhang, Rui; Jing, Haichun; Peng, Liangcai; Feng, Shengqiu
Highlights: Sweet sorghum is a leading bioenergy crop with rich soluble sugars and high biomass. Diverse sweet sorghum samples are suitable for a stable and consistent NIRS assay. Nine calibration optimal equations of NIRS with much high R 2, R 2 cv and RPD values. NIRS simultaneous assay for stalk sugars, bagasse saccharification and wall polymers. NIRS applicable for high-throughput screening of bioenergy sweet sorghums. Abstract: In this study, 123 sweet sorghum ( Sorghum bicolor L. ) accessions and 50 mutants were examined with diverse stalk soluble sugars, bagasse enzymatic saccharification and wall polymers, indicating the potential near infrared spectroscopy (NIRS) assay for those three important parameters. Using the calibration and validation sets and modified squares method, nine calibration optimal equations were generated with high determination coefficient on the calibration ( R 2 ) (0.81–0.99), cross-validation ( R 2 cv ) (0.77–0.98), and the ratio performance deviation ( RPD ) (2.07–7.45), which were at first time applied by single spectra for simultaneous assay of stalk soluble sugars, bagasse hydrolyzed sugars, and three major wall polymers in bioenergy sweet sorghum.